Free Trade and Pollution in the Manufacturing Industry in Mexico: A Verification of the Inverse Kuznets Curve at a State Level - Jáuregui Nolen, Elena Catalina; Salazar Cantú, José de Jesús; Rodríguez Guajardo, Raymundo Cruz; González García, Héctor (Universidad Autónoma de Nuevo León, 2010)
There has been a long debate about the effects that free trade has on pollution. Most empirical analysis on this topic has focused at the national level. The objective of this study is to see if there is a relationship between the pollution generated by the manufacturing industry in each of Mexico’s 32 states and the North American Free Trade Agreement (NAFTA). This was done via panel data regression models using information on pollution, income, and degree of trade from each of the states for the years 1993 and 2000. The pollution index level was constructed using the Industrial Pollution Projection System from the World Bank. In general we found a positive relationship between trade liberalization and pollution caused by manufacturing. Furthermore, we found that income and pollution follow the relationship expressed in the Environmental Kuznets Curve. JEL classification: F18, Q56